Research in economic history. Vol. 27 - Field, Alexander J. (Research in economic history,, 2010)
Amongst other European and US focussed topics, Volume 27 addresses: the macroeconomic aggregates for England, 1209-2004; capital accumulation in Spain, 1850-2000; British Estate Acts, 1600 to 1830. Notably there is also a contribution from the late William Parker , who chapter discusses historical trends in food consumption in the United States.